Fluorescence detection of biological objects with ultraviolet and visible light-emitting diodes - Kurilcik, Natalija; Vitta, Pranciskus; Zukauskas, Arturas; Gaska, Remis; Ramanavicius, Arunas; Kausaite, Asta; Jursenas, Saulius (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Recent progress in fabrication of semiconductor light emitting diodes (LEDs) allows these devices to be used for excitation of fluorescence of aromatic amino acids and other biofluorophores. In our work, a deep-UV UVTOPTM LED (280 nm) developed by Sensor Electronic Technology, Inc., was used for fluorescence characterisation of natural protein fluorophores in enzyme glucose oxidase (GOx) and in Bacillus subtilus dry spores (B. subtilus). A longer-wavelength Nichia LED (375 nm) and high-power LuxeonTM LED (450 nm) were used for fluorescence detection of enzyme cofactors. Combined spectral and fluorescence lifetime measurements using selective LED excitation enabled us to recognise the impact of specific autofluorophores in complex biological systems. Inexpensive LED-based fluorescence detectors can be used in designing biosensors and detect-to-warn systems.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 193-198
Keywords: optyka; semiconductor light emitting diodes (LEDs); UV LEDs; fluorescence lifetime; frequency-domain measurements; glucose oxidase; Bacillus subtilus spores